ENTREVISTA CON ESPERANZA AGUILAR DE FLÓREZ - OLGA LUCIA CASTIBLANCO ABRIL (Universidad Distrital Francisco José de Caldas, 2011)
Brief biography:Degree in Physics at Industrial University of Santander, Colombia. Master in Education, and Master in Physics at Industrial University of Santander. She has served as professor at UIS for 32 years. She is currently professor of physics at UIS for engineering students and educational workshop on teaching physics for physicists.Questions for professor Aguilar.1. Why did you decide to do research in physics education?2. How do you sum up your proposal about use of experimentation in physics teaching?3. How do you think should be used to learn physics in the training of people ?4. How do you see the future about research in physics education?5. Will we have soon your next book?